What You Need to Know about Economics. - Buckley, George; Desai, Sumeet (Capstone Publishing (A Wiley company), 2011)
George Buckley & Sumeet Desai: What You Need To Know About Economics Economics Matters. But with confusing things like GDP and interest rates, it's often hard to get you head around. So What do you really need to know about economics? Find out:What economic growth is and why it mattersHow inflation happensHow jobs are created and lostHow the property market worksWhat central banks do and how it affects the rest of usThe impact of government spending on the economy What You Need to Know About Economics cuts through the theory to help you to do your job and understand the world around you better.
Keywords: ekonomie -- teorie; economics (theory); elektronické knihy; příručky; electronic books; handbooks and manuals